(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
Gaucher disease is a sphingolipidosis that leads to an accumulation of glucosylceramide. The objective of this study was to develop a methodology, based on the extraction, purification and quantification of glucosylceramide from blood plasma, for use in clinical research laboratories. Comparison of the glucosylceramide content in plasma from Gaucher disease patients, submitted to enzyme replacement therapy or otherwise, against that from normal individuals was also carried out. The glucosylceramide, separated from other glycosphingolipids by high performance thin layer chromatography (HPTLC) was chemically developed (CuSO4 / H3PO4) and the respective band confirmed by immunostaining (human anti-glucosylceramide antibody / peroxidase-conjugated secondary antibody). Chromatogram quantification by densitometry demonstrated that the glucosylceramide content in Gaucher disease patients was seventeen times higher than that in normal individuals, and seven times higher than that in patients on enzyme replacement therapy. The results obtained indicate that the methodology established can be used in complementary diagnosis and for treatment monitoring of Gaucher disease patients.